If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 1) = 2 Reorder the terms: 2(1 + 5x) = 2 (1 * 2 + 5x * 2) = 2 (2 + 10x) = 2 Add '-2' to each side of the equation. 2 + -2 + 10x = 2 + -2 Combine like terms: 2 + -2 = 0 0 + 10x = 2 + -2 10x = 2 + -2 Combine like terms: 2 + -2 = 0 10x = 0 Solving 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '10'. x = 0.0 Simplifying x = 0.0
| -3(7-2x)=39 | | -7(-3+5x)=21 | | 5(-2-4x)=70 | | 0=t^3+t^2-10t+8 | | 7(6x-2)=-476 | | 5(-8+7x)=-40 | | -5(-2x+4)=90 | | -5(1x+7)=-20 | | 2(1+1x)=24 | | 19/20*32 | | -5(2+7x)=-10 | | 3.14*4*1= | | 32*19/20 | | 15a^2+7ab-2b^2=0 | | 3x-3=-38-2x | | 4(3+3c)=56 | | 6(x+1)(x+1)-14=0 | | 10(x-2)=-2+40 | | 10+4x=7x+4 | | -12=-2x+3 | | 8+x=-4x-32 | | (5/7)=(x/21) | | 4y=-2x-1 | | 0.009/9 | | x+4=76-5x | | 33-x=33 | | 0.09/18 | | 7x-3=3x+41 | | 11(-5+4)= | | -y-7=-12 | | 576+100=x | | 2+6x+6x=26 |